Emerging awareness on the importance of skeletal muscle in liver diseases: time to dig deeper into mechanisms!. (12th February 2019) - Nachit, Maxime; Leclercq, Isabelle A.
Abstract: Skeletal muscle is a tissue that represents 30–40% of total body mass in healthy humans and contains up to 75% of total body proteins. It is thus the largest organ in non-obese subjects. The past few years have seen increasing awareness of the prognostic value of appreciating changes in skeletal muscle compartment in various chronic diseases. Hence, a low muscle mass, a low muscle function and muscle fatty infiltration are linked with poor outcomes in many pathological conditions. In particular, an affluent body of evidence links the severity, the complications and mortality of chronic liver disease (CLD) with skeletal muscle depletion. Yet it is still not clear whether low muscle mass is a cause, an aggravating factor, a consequence of the ongoing disease, or an epiphenomenon reflecting general alteration in the critically ill patient. The mechanisms by which the muscle compartment influences disease prognosis are still largely unknown. In addition, whether muscle alterations contribute to liver disease progression is an unanswered question. Here, we first review basic knowledge about muscle compartment to draw a conceptual framework for interpreting skeletal muscle alteration in CLD. We next describe recent literature on muscle wasting in cirrhosis and liver transplantation. We then discuss the implication of skeletal muscle compartment in non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH), focusing on plausible metabolic disruption in muscle compartment that might participate in NAFLD progression. Finally, we discuss shortcomings and challenges we need to address in the near future prior to designate the muscle compartment as a therapeutic target in CLD.